DEVELOPMENT AND REPRODUCTION OF THE TWO PREDATORY MITES EUSEIUS scutalis AND TYPHLODOROMIPS swirskii (ACARI: PHYTOSEIIDAE) AS AFFECTED BY LEAF TEXTURE OF STRAWBERRY PLANTS - Sawsan Elsawi; Mahmoud Alazzazy (Arab Universities Journal of Agricultural Sciences, 2007)
The predatory phytoseiid mites Euseius scutal-is (El-Badry) and Typhlodrompis swirskii (Athias–Henriot) successfully developed and reproduced on strawberry leaves, infested with mymphs of the two-spotted spider mite Tetramychus urticae kock as prey, of both Yaeel (smooth slight hairy) and Vantana (rough dense hairy) cultivars indicating a different effect of leaf surface on their behaviour at 27o C and 70% RH.Yaeel leaf was the most appropriate surface and Vantana ones was the least. Longevity was the greatest on Yaeel (31.92 and 28.48 days) and the shortest on Vantana (19.40 and 15.50 days) for each predator, respec-tively. The total number of eggs/ female was 39.00 and 41.34 on Yaeel and 21.02 and 19.68 on Vantana, respectively. Population of the two pred-ators multiply 29.21 and 27.41 in a generation time of 15.78 and 13.93 days on Yaeel, whilst they were (Ro= 14.77 and 14.79) and (T= 14.26 and 12.55 days)on Vantana, respectively. Life table parameters also indicated that the smooth Yaeel leaves are better host-plants for predators in terms rm and erm. Trichomes characteristics on midrib and blade of Yaeel and Vantana strawberry leaves were determined